2019
DOI: 10.5758/vsi.2019.35.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Treatment Result Between Anticoagulation Alone and Catheter-Directed Thrombolysis Plus Anticoagulation in Acute Lower Extremity Deep Vein Thrombosis

Abstract: Purpose Deep vein thrombosis (DVT) is the third most common cause of cardiovascular morbidity and mortality. Anticoagulation has been the primary treatment modality for acute DVT. However, catheter-directed thrombolysis (CDT) has recently become widely accepted as an additional therapy to anticoagulation. We assessed comparative outcomes in patients with acute DVT who underwent anticoagulation therapy alone (ACA) group and those treated with CDT group. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, this study only included patients with proximal deep vein thrombosis and not all types of VTE. Another study by Young et al (2019) found that the use of anticoagulation therapy, including the use of oral anticoagulants, was associated with a lower risk of VTE recurrence, but this study did not compare the efficacy of anticoagulation therapy with that of thrombolytic therapy or catheter-directed thrombolysis [32].…”
Section: Discussionmentioning
confidence: 93%
“…However, this study only included patients with proximal deep vein thrombosis and not all types of VTE. Another study by Young et al (2019) found that the use of anticoagulation therapy, including the use of oral anticoagulants, was associated with a lower risk of VTE recurrence, but this study did not compare the efficacy of anticoagulation therapy with that of thrombolytic therapy or catheter-directed thrombolysis [32].…”
Section: Discussionmentioning
confidence: 93%
“…Data for CDT in acute DVT treatment was conflicting because the evidence was difficult to interpret. Studies used different endovascular techniques, had different follow‐up periods, and showed conflicting results 5‐16 …”
Section: Introductionmentioning
confidence: 99%
“…Studies used different endovascular techniques, had different follow-up periods, and showed conflicting results. [5][6][7][8][9][10][11][12][13][14][15][16] When an acute DVT is not recanalized, the venous obstruction and resultant damage to the venous valves causes reflux, venous hypertension, and chronic inflammatory changes and scarring. 1,17,18 This is a set up for developing postthrombotic syndrome (PTS), the primary chronic sequela of DVT in 20-50% of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Du et al reported that anticoagulation plus CDT can more effectively improve venous patency and prevent PTS than anticoagulation alone. [14][15][16] CDT is usually used to treat acute femoral vein thrombosis, but few studies have reported the efficacy and safety of CDT, especially in the treatment of acute extensive lower extremity DVT. In contrast to proximal DVT, whether anticoagulation or other methods should be used for the treatment of distal DVT remains controversial.…”
mentioning
confidence: 99%